TI_GERICHTE 12.2012.124 vom 17. Dezember 2013 , Avvocato - mandato di consulenza fiscale - esistenza del contratto - TI Tribunale d'appello (2013)
Avvocato - mandato di consulenza fiscale - esistenza del contratto